Research on Government Supervision of Primary and Secondary School Extracurricular Care Institutions in City C - Ji, Fangyu (Journal of Global Economy, Business and Finance, 2025)
China's off-campus care institutions have developed rapidly, but the lack of supervision has caused safety concerns. This study focuses on the government supervision of care institutions in City C. Using the new public management, collaborative governance and responsible government theory analysis, it is found that there is a lack of coordination among the regulatory subjects; the government's regulatory power is limited, and social forces are insufficiently involved; the laws and regulations for off-campus care institutions for primary and secondary schools are not sound; the form of supervision is limited and relies on administrative inspections; countermeasures are proposed: "departmental joint governance" and cross-departmental collaboration; with the help of social supervision, expand multi-party participation; issue relevant laws and regulations to regulate the operation of care institutions; introduce information-based supervision methods to achieve dynamic monitoring. The study aims to provide theoretical support and practical reference for improving the quality and safety level of care services in City C, and promote the all-round development of primary and secondary school students.